Kerjasama pemerintah Indonesia dan Singapura dalam pengelolaan wilayah kawasan ekonomi khusus era Joko Widodo-Jusuf Kalla (Periode 2015-2019): Cooperation between the governments of Indonesia and Singapore in the management of special economic zones during the Joko Widodo-Jusuf Kalla era (2015-2019 Period) - Achmad Achmad; Fadillah Afrivo Nasir (JOURNAL OF GOVERNMENT SCIENCE, 2022)
This research examines how the implementation and contribution of Indonesia-Singapore special economic zone cooperation on Batam, Bintan, and Karimun Islands in the era of Jokowi-Jusuf Kalla administration in 2015-2019. The research employs a qualitative descriptive method, with a library research approach by analyzing the phenomenon of developing special economic zones. The results of this study show that the development of a special economic zone between Indonesia and Singapore is a strategy of economic interest through a pattern of bilateral cooperation. The collaboration is manifested in the optimization of three regions, namely Batam, Bintani, and Karimun as investment land. Optimization is carried out with tax exemption as a form of facilitating investment services. In addition, special economic zones are also manifested in the concept of free trade in the three development areas (Batam, Bintan, and Karimun), whose contribution is in the form of growth of Gross Regional Domestic Product in each region.